A utilização do prontuário eletrônico do paciente pelos hospitais de Belo Horizonte - Juliana Lopes Dias (2006)
The Electronic Patient Record is the electronic alternative for Information storage and retrieval in the health area. According to the health literature, it is only a matter of time before the Electronic Patient Record is adopted over the regular paper-based patient records. Although there are available electronic systems in the field, Brazilian health institutions have not been able to implement a total replacement of the paper-based storage. This study intends to improve understanding of how the Electronic Patient Record has been adopted by the hospitals, as well asthe possible difficulties for its efficient management. This analysis is based on a research among the doctors and hospitals in Belo Horizonte. The conclusion proves that Electronic Patient Record is not effective, yet the doctors validate the main advantages listed by the authors in the health area, and indicate a probable replacement of the paper-based health record.